Risk, trust, trustworthiness and social preferences: perspective from Kazakhstan - Zhagparova, Akerke (2015)
In this study we investigate risk, trust, trustworthiness and social preference tendencies in Kazakhstan. Additionally the employment of a one shot strategy method for 31 countries in simple incentivised economic experiments enables us to examine the trust, trustworthiness and social preference of subjects towards specific nations, including Kazakhstan. We find that individuals show very high risk aversion tendencies while no support is found for risk seeking preferences. The trust game reveals that Kazakhstan and wealthier countries are trusted more and perceived to be more trustworthy than poorer countries. Moreover, we claim that geographical distance and language dissimilarities may not necessarily be obstacles to exhibiting trust and trustworthiness if bilateral trade relations are established and ties between diverse ethnicities are developed through their presence in Kazakhstan. The social preference game (or equality/matrix game) reveals that subjects tend to show higher egalitarian and selfish preferences than altruistic preferences.